1979
DOI: 10.1007/bf00114055
|View full text |Cite
|
Sign up to set email alerts
|

Flux-line cutting in type II superconductors

Abstract: Experimental evidence for flux-line cutting in superconductors (intersection and cross-joining of singly quantized vortices) is briefly reviewed. The interaction energy between two straight vortices tilted at an angle a (~ O)is thenshown to be finite in the London model, i.e., in the limit of vanishing core radius. Next, the activation energy and maximum interaction force are calculated for the vortices in an analytic approximation to the GinzburgLandau theory. Here two competing interactions determine the beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 19 publications
(3 reference statements)
0
36
0
Order By: Relevance
“…Since then, the force free configurations and transverse vortex motion in longitudinal currents were addressed in many theoretical works but still remain a hypothetical concept. Two crossing vortices should experience a long-range repulsion due to the λ-shell of supercurrents, while the intersection of the normal cores will provide their short-range attraction [53]. This could yield pinning of vortices by transverse vortices.…”
Section: Flux Cuttingmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the force free configurations and transverse vortex motion in longitudinal currents were addressed in many theoretical works but still remain a hypothetical concept. Two crossing vortices should experience a long-range repulsion due to the λ-shell of supercurrents, while the intersection of the normal cores will provide their short-range attraction [53]. This could yield pinning of vortices by transverse vortices.…”
Section: Flux Cuttingmentioning
confidence: 99%
“…This could yield pinning of vortices by transverse vortices. The resulting pinning potential was first assumed to be very high (~normal core condensation energy), but subsequent calculations showed only moderate values of the cutting barrier U x [53]. Account of the mutual bending of vortices near the intersection point revealed additional attraction and further reduction of U x [54][55][56][57].…”
Section: Flux Cuttingmentioning
confidence: 99%
“…The situation is more intricate when the field is applied transversally to the remnant magnetization . This effect, called either "abnormal transverse magnetic field effect", "collapse of the static magnetization" or "crossed-field demagnetisation" was observed on low-Tc wires [21,28,43], bulk (RE)BCO materials [22,25,28,33,34,40], MgB2 [44] and recently on stacks of 2G tapes [45]. Up to now, however, the exact processes of the magnetization decay in the case of a crossed field configuration are not completely identified.…”
Section: Introductionmentioning
confidence: 99%
“…Given that cutting is energetically plausible, they found that flux-line cutting is an effective disentanglement mechanism of flux lines; and that the cutting energy barrier, in the case of twisted flux lines, is lower for the rigid two-flux-lines case [11,12]. Several groups, for example, M.A.R.…”
Section: Flux-line Cuttingmentioning
confidence: 99%